Heterostructured Bismuth Telluride Selenide Nanosheets for Enhanced Thermoelectric Performance. Issue 1 (25th October 2020) - Bauer, Christoph; Veremchuk, Igor; Kunze, Christof; Benad, Albrecht; Dzhagan, Volodymyr M.; Haubold, Danny; Pohl, Darius; Schierning, Gabi; Nielsch, Kornelius; Lesnyak, Vladimir; Eychmüller, Alexander
Abstract : The n‐type semiconductor system Bi2 Te3 Bi2 Se3 is known as a low‐temperature thermoelectric material with a potentially high efficiency. Herein, a facile approach is reported to synthesize core/shell heterostructured Bi2 Te2 Se/Bi2 Te3 nanosheets (NSs) with lateral dimensions of 1–3 μm and thickness of about 50 nm. Bi2 Te3 and Bi2 Se3, as well as heterostructured Bi2 Te2 Se/Bi2 Te3 NSs are obtained via colloidal synthesis. Heterostructured NSs show an inhomogeneous distribution of the chalcogen atoms forming selenium and tellurium‐rich layers across the NS thickness, resulting in a core/shell structure. Detailed morphological studies reveal that these structures contain nanosized pores. These features contribute to the overall thermoelectric properties of the material, inducing strong phonon scattering at grain boundaries in compacted solids. NSs are processed into nanostructured bulks through spark plasma sintering of dry powders to form a thermoelectric material with high power factor. Electrical characterization of our materials reveals a strong anisotropic behavior in consolidated pellets. It is further demonstrated that by simple thermal annealing, core/shell structure can be controllably transformed into alloyed one. Using this approach pellets with Bi2 Te2.55 Se0.45 composition are obtained, which exhibit low thermal conductivity and high power factor for in‐plane direction with zT of 1.34 at 400 K. Abstract : Bi2 Te3, Bi2 Se3, and core/shell Bi2 Te2 Se/Bi2 Te3 nanosheets with lateral dimensions of 1–3 μm and thickness of about 50 nm are obtained via colloidal synthesis. Heterostructured nanosheets show an inhomogeneous distribution of the chalcogen atoms and nanosized pores. They are processed into nanostructured bulks with Bi2 Te2.55 Se0.45 composition, exhibiting low thermal conductivity and high power factor with zT of 1.34 at 400 K.